Measured Resources and Proven Reserves – Are they still Relevant? - S Juras (The Australasian Institute of Mining and Metallurgy, 2011)
The terms measured resources and proven reserves denote the highest level of estimation confidence in all of the major classification schemes. But what do they really bring to today’s project or mine with respect to production planning and expectations? Initial reserve declaration does not need measured resources, just indicated resources. Economic viability of a project is assessed on total reserves with nary a bonus for the amount of proven reserves. Production plans are based on grade and tonnage goals that may only coincidently correspond to proven reserves. So are the measured and proven categories still relevant? Historically, and almost exclusively in underground mines, companies only allowed mining in areas of proven reserves. Some companies still follow that philosophy. But many others will mine a mixture of probable and proven reserves without hesitation. Also what of the undeveloped project in a new district – what is to be made of their declared measured resources and proven reserves? Measured resources are commonly set either by some type of proximity to data scheme or a matter of ‘feel’ based on the qualified person’s experience. The parameters for reserve conversion focus on the project as a whole and then a portion becomes classified as proven reserves almost solely based on whether the resource category is measured. So should the mining industry continue to use these categories of resource and reserve classification? This paper will present arguments about making these categories once again more relevant. A more disciplined usage of these categories may re-introduce their relevancy in public disclosures of resources and reserves. As well a more consistent usage in operations may lead to increased confidence in managing production targets and costs.